Precision of landmark identification using scanned cephalometric image - Md. Lani, Ruzaini (2005)

(untitled)
This research is focused on the precision of landmark identification using scanned cephalometric images.A sample image was used to generate 5 sets of data for landmark identification. All 5 dataset were measured by the angle SNA, SNB and ArSN. 3D DOCTOR software is used for the landmark identification and the angle measurement. For each set, the angle was measured five (5) times to get the average value. The values are used to create a graph (to show the precision for the angle measurement) and also to calculate the mean and standard deviation using SPSS. The results were consistent and satisfactory.